Pet Rescue Adventures : The Unwanted Puppy - Webb, Holly; Williams, Sophy (Wilton, Connecticut : Tiger Tales, 2019)
Zoe cant help but fall in love with Bear, an adorable Bernese mountain dog puppy she meets in the park after school. Bear is large and lively and belongs to a new family in the neighborhood. Bears owners are always on the go and are grateful when Jade offers to walk Bear. But as she spends more time with him, she begins to worry that they arent able to give him the attention and exercise he needs. How can she help Bear when he isnt her dog to help?
"Originally published in Great Britain 2018 by the Little Tiger Group"--Title page verso.
Keywords: Bernese mountain dog -- Juvenile fiction; Puppies -- Juvenile fiction; Dog walking -- Juvenile fiction; Dogs -- Juvenile fiction; Pets -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Animal Fiction